Guided Inquiry Meets Audiovisual Media: Elevating Cognitive and Scientific Reasoning Skills - Nurul Kami Sani; Muhammad Fachri B. Paloloang; Dyah Rahmawati; Nurul Fitriah Aras (Universitas Cokroaminoto Palopo, 2024)
This study identifies the issues of insufficient effective teaching materials and minimal utilization of technology in education. Teaching models that do not involve student participation and the suboptimal use of educational media can hinder conceptual understanding and result in low cognitive learning outcomes and scientific reasoning skills among students. This study aims to explore the effectiveness of the Guided Inquiry model integrated with audiovisual media to enhance conceptual understanding and scientific reasoning in teaching static fluids. The research employs a pre-experimental method with a one-group pretest-posttest design, involving tenth-grade students from a senior high school in Palu during the 2023/2024 academic year. A cluster random sampling technique was used to select participants. Data collection was carried out using pretests and posttests to measure the improvement in both conceptual understanding and scientific reasoning. The results show an average normalized gain score of 0.59 for conceptual understanding, categorized as moderate, and 0.70 for scientific reasoning, categorized as high. Furthermore, a strong, significant correlation (r = 0.61) was found between conceptual understanding and scientific reasoning, indicating that the use of audiovisual media in guided inquiry enhances not only knowledge acquisition but also critical thinking skills. Therefore, this learning model is recommended for use in science education in schools to optimize students' cognitive and scientific reasoning skills. The findings of this research carry significant implications for the advancement of educational practices, particularly in the field of science learning. By highlighting key areas that require attention, the study provides insights that can inform curriculum design, teaching methodologies, and assessment strategies. This, in turn, can enhance student engagement and understanding, ultimately leading to more effective and meaningful learning experiences in science education.